2022
DOI: 10.3390/children9070930
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization of Children Aged <5 Years Due to Influenza: Study Based on the National Hospitalization Registry

Abstract: Background: Influenza constitutes a significant health care burden that can be related to an increased morbidity and mortality. The aim of the study is to show up-to-date information on influenza hospitalization cases in Poland in children aged <5 years. Methods: The data used in the study were hospitalization records from 2015–2019, which had been gathered in a Nationwide General Hospital Morbidity Study and made available by the National Institute of Public Health. Results: 8565 records of patients with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…This is unusual as respiratory infections usually afflict children <5 years old. Respiratory syncytial virus and influenza‐related hospitalizations are mainly seen in children aged <5 years 42,43 . COVID‐19 initially afflicted adults and the elderly 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unusual as respiratory infections usually afflict children <5 years old. Respiratory syncytial virus and influenza‐related hospitalizations are mainly seen in children aged <5 years 42,43 . COVID‐19 initially afflicted adults and the elderly 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus and influenza-related hospitalizations are mainly seen in children aged <5 years. 42,43 COVID-19 initially afflicted adults and the elderly. 44 Interestingly, the study by Kompaniyets et al who looked at children found that asthma was not associated with a higher risk of COVID-19 among hospitalized children, except among those aged 12-18 years.…”
Section: Risk Factors For Covid-19 Infection Among Children With Asthmamentioning
confidence: 99%
“…Therefore, it is assumed that people’s place of residence can influence the type of pathogenic microorganisms they are exposed to on a daily basis [ 32 ]. This might contribute to differences in the share of patients with CAI due to enteric pathogens, influenza viruses and MDR bacteria in villages, cities, and cities with county status [ 32 , 33 , 34 ]. Our results support this assumption for CAI due to Campylobacter , Rotavirus, MECO and MKLE; however, further research is required to determine the role of environment at a settlement in the spread of CAIs.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations available have found that CAIs due to MDR bacteria were the most frequent among the elderly, whereas community-acquired influenza and enteric diseases affected both children and elderly [ 4 , 8 , 10 , 12 , 27 , 29 ]. In addition, previous studies have suggested that there can be differences in the spread of pathogenic microorganisms causing CAI between the population living in urban and rural areas [ 32 , 33 , 34 ]. However, data on the share of patients with CAI due to enteric pathogens, influenza viruses and MDR bacteria living in settlements with different characteristics are limited, even in developed countries [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation